Rekonstruksi Manajemen Bisnis Syariah Melalui Pendekatan Paradigma Pendidikan Islam - Muhammad Abrori (Prodi Manajemen Bisnis Syariah, 2026)
This study aims to reconstruct the concept of Islamic business management through an Islamic education paradigm approach as an effort to strengthen the foundation of values, ethics, and business objectives oriented towards public interest. The main focus of this research is to integrate spiritual, moral, and social dimensions into sharia business managerial practices so that they are not solely profit oriented but also focused on shaping the character of business actors. The research method used is a qualitative approach with a library research type, through critical analysis of relevant literature, including Islamic business management theory, the Islamic education paradigm, and the concepts of values and ethics in Islam. The results of the study show that the Islamic education paradigm is capable of providing a holistic epistemological and axiological framework for Islamic business management. This reconstruction produces an Islamic business management model that emphasizes the internalization of the values of tauhid, morals, justice, and social responsibility as operational principles, thereby supporting the creation of sustainable and ethical business practices.